Development of Sustained Release Matrix Tablets A comparative study of natural and synthetic polymers - Sushma, Nakhate; Sushma, Nakhate; Swamini, Dighe; Chormale, Rahul; Mohini, Mane (Journal of Neonatal Surgery, 2025)
The present study focuses on the development and evaluation of Pioglitazone sustained-release matrix tablets using both natural (pectin) and synthetic (HPMC) polymers. The formulation was prepared by direct compression, and drug-excipient compatibility was assessed using FTIR spectroscopy, confirming no significant interactions. Micromeritic properties, including angle of repose, bulk density, and Carr’s index, indicated good flowability and compressibility, ensuring uniform tablet formation.Post-compression evaluation parameters such as hardness, friability, disintegration time, and wetting time were within acceptable limits, with formulations F2 and F4 exhibiting optimal characteristics. In vitro dissolution studies conducted in 0.1N HCl using USP Type I apparatus showed that formulations F5 and F6 demonstrated the highest drug release (95.88% and 88.22% at 60 min, respectively), making them potential candidates for immediate-release formulations.The study concludes that the selected polymers effectively controlled drug release, improving therapeutic efficacy and patient compliance. The optimized formulations can be further explored for in vivo pharmacokinetic studies to establish bioavailability and long-term stability. This research provides a comparative approach between natural and synthetic polymers in sustained-release drug delivery systems, ensuring an efficient and controlled drug release profile for improved diabetes management.